Occipital plagiocephaly: unilateral lambdoid synostosis versus positional plagiocephaly. Issue 2 (1st October 2014) - Linz, Christian; Collmann, Hartmut; Meyer-Marcotty, Philipp; Böhm, Hartmut; Krauß, Jürgen; Müller-Richter, Urs D; Ernestus, Ralf-Ingo; Wirbelauer, Johannes; Kübler, Alexander C; Schweitzer, Tilmann
Abstract : Objective: We defined parameters that could differentiate between positional and synostotic plagiocephaly and defined a diagnostic chart for decision making. Design: Prospective study. Setting: We examined 411 children with non-syndromic skull abnormalities between January 2011 and December 2012. Participants: A total of 8 infants under 1 year of age with proven unilateral non-syndromic lambdoid synostosis (LS) and 261 children with positional deformity were examined to outline the specific clinical features of both diagnoses. After clinical examination, an ultrasound revealed either a closed suture suggestive of LS or a patent lambdoid suture suggestive of positional deformity. For patients with synostosis, plain radiographs, MR imaging and follow-up examinations were performed. In cases of open sutures, only follow-ups were completed. Main outcome measure: Clinical, imaging, genesis and treatment differences between positional plagiocephaly and LS. Results: In all 8 cases of unilateral LS and 258 cases of positional plagiocephaly, the diagnosis was established by clinical examination alone. In three cases of positional plagiocephaly, diagnosis was determined after an additional ultrasonography. MR imaging revealed a unilateral tonsillar herniation in five of the eight children with LS and hydrocephalus in one child. Conclusions: We have suggested a list of clinical features that specify the underlying cause of posterior plagiocephaly. An additional ultrasound scanning confirmed the diagnosis without any risks of ionising radiation or sedation as in a CT scan.